Perancangan Sistem Monitoring Kehadiran Mahasiswa Pada Laboratorium FTKI UNAS Menggunakan Teknologi RFID - Singgih Yulianto Bastian; Agung Triayudi; Aris Gunaryati (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
The recording of student attendance at the FTKI UNAS laboratory is still done manually which causes UNAS to have to input a large amount of attendance data every day. This often results in recording errors caused by human error, not to mention if there is fraud by manipulating attendance data. This study uses a microcontroller to design a student attendance monitoring system digitally by identifying student code from the RFID Tag. The system is designed using RFID and NodeMCU modules which will be sent to the MySQL database and will be displayed on the website page. The test results from 100 data obtained 100% identification success with an average reading distance of 4cm. of 100 presence test data, the system can store data with 100% accuracy for the corresponding data, and can read the presence of errors with 100% accuracy.